2021
DOI: 10.1108/cg-10-2020-0472
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and financial performance: bidirectional relationship and mediating effect of customer loyalty: investigation in Sweden

Abstract: Purpose The study is based on a hybrid model composed of accounting and business data and is amongst the first to test the impact of corporate social responsibility (CSR) performance on the financial performance of the company, as well as the impact of financial performance on CSR performance. The bidirectional logic chosen by the study is rarely adopted in the global context and has never been tested in the Swedish context. Moreover, the purpose of this paper is to test the mediating effect of customer loyalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 103 publications
1
4
0
Order By: Relevance
“…The bidirectional relationship between the CSR disclosure and the financial performance has also been investigated. Hichri and Ltifi (2021) confirmed that these two variables have a positive and reciprocal impacts on each other. This result indicates that the CSR activities undertaken by the company improve its financial performance.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 56%
“…The bidirectional relationship between the CSR disclosure and the financial performance has also been investigated. Hichri and Ltifi (2021) confirmed that these two variables have a positive and reciprocal impacts on each other. This result indicates that the CSR activities undertaken by the company improve its financial performance.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 56%
“…Therefore, disclosing more information about the company’s social performance receives the respect of stakeholders, which improves the company’s performance in the financial market (Naseem et al , 2019). In this sense, ESG complied firms are more likely to achieve higher returns and better performance by appeasing the expectations of different groups in the financial markets (Ben Saad and Belkacem, 2022; Hichri and Ltifi, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Engaging in nonfinancial activities is one of the major tactics that enterprises must undertake to draw more stakeholders’ attention (Amoah and Eweje, 2022; Ananzeh et al , 2022). Those nonfinancial activities (such as sustainability and environmental activities) that focus on a broader segment of stakeholders rather than just shareholders have been proposed to increase financial performance (Hichri and Ltifi, 2021; Ben Saad and Belkacem, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…present the effect of social and ethical practices correlated to the ESG scores. Additionally,Hichri and Ltifi (2021) demonstrate the relevance of CSR in the financial performance of Sweden firms Alareeni and Hamdan (2020). study how ESG scores affect the US S&P 500-listed firms.…”
mentioning
confidence: 99%